To run the world the Kremlin's Cold War bid for global power - Radchenko, Sergey (Cambridge University Press, 2024)
"What would it feel like To Run the World? Soviet rulers spent the Cold War trying desperately to find out. Perennial insecurities, delusions of grandeur, and desire for recognition propelled Moscow on a headlong quest for global power, with dire consequences and painful legacies that continue to shape our world."
Keywords: Ost-West-Konflikt; Außenpolitik; Machtpolitik; Sowjetunion; Soviet Union / Foreign relations / 1945-1991; Soviet Union / Politics and government / 1945-1991; Cold War; URSS / Relations extérieures / 1945-1991; URSS / Politique et gouvernement / 1945-1991; Guerre froide